Pudendal flap—a good option for creating neo-scrotum after Fournier's gangrene: a case series. Issue 11 (14th November 2020) - Khanal, Bhawani; Agrawal, Sunit; Gurung, Roshan; Sah, Suresh; Gupta, Rakesh Kumar
Abstract: Scrotal skin loss following Fournier's gangrene is very distressing to the patients. The management is complex and challenging shown by the multiplicity of flaps and techniques described in the literature. We included a total of 14 patients with the diagnosis of Fournier's gangrene over a period of 1 year in our department. We used a modified pudendal thigh flap to reconstruct neo-scrotum in patients with scrotal defects resulting from excision and debridement of Fournier's gangrene. The average age group of the patients in our study was 41.8 years. The average body mass index in our study was 22.36 kg/m 2 . The average defect size in our study was 7.05 × 13.07 cm 2 . There was a single case of flap necrosis. Modified pudendal thigh flap produces a neo-scrotum that looks natural in appearance, provides good quality skin cover and cushion to the testes as well as protective sensation.